Exploring the Synergistic Role of Zinc in NPK Fertilization on the Agronomic Performance of Safflower (Carthamus tinctorius) - Muhammad Alamgeer; Hassan Munir; Saddam Hussain; Sudeep Adhikari; Walid Soufan; Jahangir Ahmed; Maryam Aslam; Saeed Rauf (Horticulturae)
Safflower is a multipurpose, underutilized annual crop that could be an alternate oilseed crop for normal and marginal lands around the world. Zinc as a nutrient plays a critical role in enzyme activity and nutrient absorption, leading to improved productivity and quality of oilseeds. However, imbalances between NPK and Zn can result in antagonistic interactions, leading to nutrient deficiencies. Therefore, this field experiment at the University of Agriculture, Faisalabad, Pakistan, was conducted to explore the synergistic effects of NPK and Zn on safflower growth, yield, and oil content. Safflower accession (UAF-SAFF-100) was treated with ten different combinations of zinc and NPK having different concentrations, i.e., T0 = control, T1 = NPK at 40:40:40 kg ha−1, T2 = NPK at 50:50:40 kg ha−1, T3 = NPK at 60:60:40 kg ha−1, T4 = NPK at 70:70:40 kg ha−1, T5 = NPK at 80:80:40 kg ha−1, T6 = T1 + zinc at 7.5 kg ha−1, T7 = T2 + zinc at 7.5 kg ha−1, T8 = T3 + zinc at 7.5 kg ha−1, T9 = T4 + zinc at 7.5 kg ha−1, and T10 = T5 + zinc at 7.5 kg ha−1. The results indicated that the application of T9 (NPK @ 70:70:40 kg/ha−1 + zinc @ 7.5 kg/ha−1) showed the most promising results in terms of growth and yield attributes. This treatment significantly improved key metrics such as capitulum diameter, the number of capitula per plant, seed yield, petal yield, and oil content. Thus, this treatment (T9) is proposed as an effective strategy for enhancing safflower growth and productivity, particularly in semi-arid regions. This study underscores the importance of optimizing nutrient management to achieve superior crop performance and suggests that tailored NPK and Zn applications can be a promising approach to maximizing safflower yield and oil quality.